Entrepreneurship and entrepreneurial innovation of university students, Amazonas, Peru - Davila, Manuel Antonio Morante; Pantaleon, Alex Javier Sanchez; Caro, Omer Cruz; Reyes, Elena Irene Bautista; Ocampo, Patricia Escobedo (International Journal of Innovative Research and Scientific Studies, 2024)
This study aims to investigate the influence of entrepreneurship on innovation competencies in students. Using a descriptive, non-experimental research design with a quantitative relational approach, the research involved a participant pool of students from the Universidad Nacional Toribio Rodríguez de Mendoza de Amazonas, totaling 310 individuals. To stimulate entrepreneurship that contributes to economic growth, it is essential to nurture entrepreneurship competencies among university students. Data collection utilized a Likert scale questionnaire, and the analysis employed SPSS and PLS statistical software. Results revealed that 60.7% of students fell within the 21 to 25 age range, with 50% receiving an income between S/. 500 to S/. 1500 soles from their parents and 48.8% obtaining income from the Cuna Más program. The PLS findings reveal a substantial impact of entrepreneurship on university students' innovation competencies, with correlations of 0.756 for knowledge generation, 0.736 for knowledge assimilation, 0.699 for knowledge partnership, and 0.756 for reorganization of knowledge. This highlights the critical importance of emphasizing entrepreneurial skills in university education. The research addresses a global literature gap on the impact of entrepreneurial competencies in establishing innovative businesses, aiming to provide empirical evidence linking open innovation dynamics and entrepreneurship. Anticipated outcomes underscore how pedagogical approaches can enhance students' capacity to generate new value for organizations or society through fostering innovative thinking and behavior.